Selecting of brands mobile phone using Analytic Hierarchy Process (AHP) method : a case study of Universiti Malaysia Pahang - Nor Anira, Ismail (2014)
The aim of this research is to study about selecting of brands mobile phone using analytic hierarchy process (AHP) method among Faculty of Industrial Management (FIM) students. For the functionality, physical characteristics, technical features, basic requirement and customer excitement are set as the criteria. Then, the Apple/I-phone brand, Sony brand, Nokia brand and also Samsung brand is the alternative in this research. One hundred and sixty-nine of degree students in Faculty of Industrial Management (FIM) were surveyed by questionnaire. The collected data was analyzed by using Microsoft Excel and also Microsoft Silverlight software. Results show that the functionality is become the best criteria and the Samsung brand is become the top ranking as an alternative in this research